Notice of Compliance with Conditions: A Policy in Limbo - Joel Lexchin (Law & Governance, 2007)
[This article was originally published in Healthcare Policy / Politiques de Santé, Volume 2, Number 4.] Since 1998, the Therapeutic Products Directorate (TPD) has had a policy termed the Notice of Compliance with conditions (NOC/c) in order to allow earlier marketing of promising drugs for serious conditions before the drugs have definitively demonstrated clinical efficacy. Drugs approved under the NOC/c must undergo post-marketing trials to show clinical benefits. The reasons that some drugs receive a NOC/c are not always apparent, and the TPD releases only general information regarding the conditions that need to be fulfilled. Some drugs have fulfilled their conditions in under 1.4 years, but others had unfulfilled conditions after seven years. Doctors may not be aware that drugs are marketed with a NOC/c nor that some drugs have had their NOC/c withdrawn, and as a consequence may be prescribing inappropriately for their patients. Other jurisdictions have similar policies but with stricter and more transparent requirements. Adopting these provisions, along with other reforms, could help ensure that the NOC/c policy meets it objectives. [To view the French abstract, please scroll down.]